2009
DOI: 10.1182/blood.v114.22.1410.1410
|View full text |Cite
|
Sign up to set email alerts
|

New Formula for the Differentiation Between Iron Deficiency Anemia and Thalassemic Carrier in Thalassemic Prevalence Areas: A Study in Healthy School-Age Children.

Abstract: 1410 Poster Board I-432 INTRODUCTION: In Thailand, the prevalences of iron deficiency anemia (IDA) and thalassemia carrier are high in the range between 20-50%. Screening of both disorders may show the similar results of low hemoglobin (Hb) and mean corpuscular volume (MCV). Therefore, additional laboratory investigations such as ferritin level, percentage of iron saturation, Hb analysis and DNA study may be required for the definite diagnosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 0 publications
1
29
1
Order By: Relevance
“…17,18 In the present study, the high prevalence of IDA observed in the school-aged group was similar to that observed in a previous study in 2014. 5 The Ret-He level observed in the present NC group was slightly lower compared with that in adults. 6,9 This is expected because the Hb level in children is typically lower than in adults.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…17,18 In the present study, the high prevalence of IDA observed in the school-aged group was similar to that observed in a previous study in 2014. 5 The Ret-He level observed in the present NC group was slightly lower compared with that in adults. 6,9 This is expected because the Hb level in children is typically lower than in adults.…”
Section: Discussioncontrasting
confidence: 52%
“…[1][2][3][4] In Thailand, a 2012 study in school-aged children reported incidence rates of ID and iron deficiency anemia (IDA) at 38% and 12%, respectively, while the incidence rates of thalassemia trait and disease in these populations were reported at 32% and 3%, respectively. 5 Currently, the diagnosis of IDA and of thalassemia typically involves the use of traditional hematology parameters. Because both diseases share similar hematological findings of low hemoglobin (Hb) and mean corpuscular volume (MCV), further testing should be done in order to differentiate between the two diseases, namely, iron study, Hb typing, and genetic testing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So, our goal is to develop a new mathematical model to study the effect of the blood variables, sex, and age on the types of anemia. Our model, different from the mathematical models given in the literature [15][16][17][18][19], has also been successfully used in the prediction of several types of anemia through a large group of blood variables, sex, and age.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, many studies were carried out [16,18,[21][22][23] by using relatively less number of input variables to predict the type of anemia. The methods used in the corresponding studies produced relatively less accurate results.…”
Section: Introductionmentioning
confidence: 99%